A Case Study of Students’ Wellbeing in a Post-Secondary School in Malta - Josephine Ebejer Grech (Language, Literature and Education: Research Updates Vol. 2, 2025)
This study aims to fill a gap in research about the wellbeing of post-secondary students in Malta. It explores what students understand by the term wellbeing. Guided by Bradburn’s studies on Subjective Wellbeing (SWB) theory, which emphasises the role of personal experiences in shaping wellbeing, findings can contribute to policy or practice, particularly regarding school improvements. Understanding and implementing the most appropriate strategies can positively affect academic performance, mental health, and student retention. This case study adopts a qualitative research methodology using semi-structured interviews as an ontological stance. Convenience sampling was used. Data analysis employs the Braun-Clark (2021) method. To draw results and conclusions, an inductive interpretivist epistemological stance analysis approach is utilised. Results show that the interviewed students align with the positive factors outlined in the third domain of the 17 Sustainable Development Goals (SDGs) within the Agenda for Sustainable Development. Positive factors influencing wellbeing included personal, social, and cognitive aspects, with teacher support emerging as the most significant positive influence, while workloads and deadlines were identified as major negative factors. Students proposed several recommendations, including reducing their workload and deadlines, among other suggestions. In the concluding reflection, the researcher points out that perceived negative factors might not necessarily be inherently negative. Supportive teachers, identified as the most positively influential factor in schools, may play a key role in mitigating major perceived negative factors, such as heavy workloads and deadlines. The researcher questions whether decreasing workloads and deadlines effectively prepares students for future endeavours. These conclusions highlight the need for a further study to identify the most appropriate strategies for cultivating a growth mindset, fostering resilience through positive psychology, and equipping students with effective coping strategies.